PENGARUH KEPEMIMPINAN ETIS DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PT MASAJI TATANAN KONTAINER INDONESIA (MTKI) - Sintia; Ahmad Fadli; Roni Juliansyah (Jurnal Mahkota Bisnis (Makbis), 2024)
This research aims to determine the extent of the influence of Ethical Leadership and Organizational Commitment on Employee Performance at PT Masaji Tatanan Kontainer Indonesia (MTKI). Data collection methods involved distributing a Google Form questionnaire to a sample of 55 employee respondents. The analysis used includes validity tests, reliability tests, classical assumption tests, statistical tests, and MRA tests. Based on the research results, Ethical Leadership partially has a positive effect on Employee Performance with a t-value > t-table (7.414 > 1.673) and a significance level of 0.000, which is less than 0.05. Organizational Commitment partially has a positive effect on Employee Performance with a t-value > t-table (3.747 > 1.673) and a significance level of 0.000, which is less than 0.05. The contribution of Ethical Leadership and Organizational Commitment to Employee Performance is 82%, while the remaining 18% is influenced by other variables outside of this study